The impact of the case-based learning model and learning motivation on learning outcomes - Fahmi, Ahmad Ihfan Khalif; Degeng, Made Duananda Kartika; Soepriyanto, Yerry (Univeritas Papua, 2025)
This study aims to explore the impact of implementing the case-based learning (CBL) model and student motivation on academic achievement in mathematics. The background of this research is the low interest and motivation of students in mathematics learning, which affects their academic performance. The research design uses an experimental method with a post-test approach. The subjects of the study consisted of 40 eighth-grade students from a junior high school, divided into experimental and control groups. The findings indicate that the application of the CBL model significantly improved students' learning outcomes compared to conventional learning, with a significance value of 0.000. On the other hand, students with high motivation showed better results than those with low motivation (significance value of 0.010). However, no significant interaction was found between the learning model and motivation in influencing learning outcomes. Based on these findings, it can be concluded that CBL is effective in improving mathematics learning outcomes, while motivation also plays an important role in students' academic achievement.